A new hybrid control algorithm design and simulated for longitude and latitude movements stabilization of nonlinear fixed-wing UAV - Faizan Ahmed Warsi (School of Mechatronic Engineering, Universiti Malaysia Perlis, 2014)
In this thesis a new hybrid control algorithm is presented for longitudinal and lateral movements controlling of small fixed-wing UAV. The proposed control technique is developed by joining the PID algorithm with PD-LQG algorithm to stabilize the small fixed-wing UAV flight under sensor noisy conditions and external disturbance circumstance. For verifying the performance of proposed control strategy it is simulated on 'Yardstick' type small fixed wing UAV. The simulation are performed and analyzed under different windy and noisy conditions. MATLAB Simulink with its Aerosim block set is used to execute all the simulation. The simulation results demonstrates that the proposed control technique performed exceptionally well under perturbed conditions and its performance is much better than available traditional algorithms under uncertainty conditions.